Channel Utilization of a Half-Duplex ARQ Protocol for Packet Radio Channels - Abaya, Efren F. (Philippine Engineering Journal; Vol 12 No 2 (1991), 2021)
ARQ is a common error control method for terrestrial data transmission. The different types of ARQ are reviewed, and channel utilization characteristics are summarized. A half-duplex go-back-NARQ method is presented as a model for the AX.25 ARQ protocol used in packet radio, and an equation for channel utilization is derived and analyzed